Scotland's Choices - McLean, Iain (Edinburgh University Press, 2014)
Everything you need to know about Scotland's independence referendum: the options, the big issues and what happens next. New for this edition. Contains new details not available for the first edition: the date, the question, and many related issues Analyses the recently published Scottish Government whitepaper, 'Scotland's Future : Your Guide to an Independent Scotland' - the SNP's vision of what will happen should the vote be Yes Includes new sections evaluating the policy positions set out by the Scottish and UK Governments Scotland faces its biggest choice since the 1707 union - should Scotland be an independent country? The Yes and No campaigns are well under way but with the vote looming closer the information available to the public is still limited. The Scottish people will have to make their own judgments, and so they need to have the issues explained as clearly as possible without spin or bias. What will happen after the referendum? How will Westminster and the rest of the UK respond? What happens if the vote is 'No'? Is it even clear what independence will mean? What about the oil? What will the currency be? What will happen to the Old Age Pension pot if the UK splits? Scotland's Choices, now fully revised for the critical last few months before the referendum, does just that. Written by one former civil servant, one academic and one think-tanker - one a resident Scot, one a Scot living in England and one an Englishman - the authors clearly explain the issues you may not have considered and detail how each of the options would be put into place after the referendum. Key Features. Lays out the facts in clear language with no political agenda Written by leading experts at the heart of the political process who are equipped to ask hard questions about the options Explains the little-understood Scotland Act, which will come into force if the vote is No Looks at the key issues that must be addressed if the vote is Yes: public spending, tax and welfare, EU membership, the future of Faslane, the currency, financial regulation, oil revenues and many others